Circulating strains of Human Respiratory Syncytial virus in Central and South America. (2011)
ABSTRACT: Human respiratory syncytial virus (HRSV) is a major cause of viral lower respiratory tract infections among infants and young children. HRSV strains vary genetically and antigenically and have been classified into two broad subgroups, A and B (HRSVA and HRSV-B, respectively). To date, little is known about the circulating strains of HRSV in Latin America. We have evaluated the genetic diversity of 96 HRSV strains by sequencing a variable region of the G protein gene of isolates collected from 2007 to 2009 in Central and South America. Our results show the presence of the two antigenic subgroups of HRSV during this period with the majority belonging to the genotype HRSV-A2.